Histoplasmosis and multicentric lymphoma in a Nubian goat. (September 2019) - Schlemmer, Samantha N.; Fratzke, Alycia P.; Gibbons, Philippa; Porter, Brian F.; Mansell, Joanne; Ploeg, Richard J.; Rodrigues Hoffmann, Aline; Older, Caitlin E.; Clark, Sabrina D.
Following treatment for pneumonia, a 1-y-old female Nubian goat was presented because of a persistent fever for 3 mo and peripheral lymphadenopathy for 1 mo. Cytology and histology of the superficial cervical and prefemoral lymph nodes demonstrated a moderate-to-marked "left-shifted" lymphoid population, suggestive of lymphoma, and extremely rare extracellular, 2–4 µm, oval, basophilic yeast, consistent with Histoplasma capsulatum . On immunohistochemistry, >95% of the lymphocytes demonstrated positive cytoplasmic and membranous immunoreactivity for CD3. Histoplasma spp. urine antigen and serum antibody testing were positive and negative, respectively. Panfungal PCR and sequencing of DNA extracted from scrolls of formalin-fixed, paraffin-embedded tissue yielded matches to H. capsulatum with 99–100% identity. Given the poor prognosis and persistent pyrexia, the animal was euthanized. Postmortem examination confirmed concurrent multicentric, intermediate-size, T-cell, lymphoblastic lymphoma and histoplasmosis; lesions consistent with intestinal coccidiosis and suspected pulmonary Rhodococcus equi were also noted. Although dimorphic fungi have been described previously in goats, lesions of Histoplasma spp. had not been documented in this species, to our knowledge. Given the low disease burden, it is suspected that the lymphoma was primary, leading to an immunocompromised state and development of secondary, opportunistic infections.